Teachers’ Perception About Counseling Services in Their Schools: A Study Based on Kilinochchi Education Zone in Sri Lanka - Nithlavarnan, A. (University of Jaffna, 2017)
Northern Province of Srilanka, facing several educational problems after the postwar situation. Out of these, increasing demand of counseling services for school children due to several reasons such as changing the social, economic and culture situation of the country and problems related to family structure, family violence, school curriculum, peer group and advancement of technology. This study attempts to identify the teachers’ perception about counseling services in their schools. 47 teachers selected from Kilinochchi Educational zone as survey sample. Questionnaire used as a data collection tool. The problems such as irregular attendance to the schools. Late comers to the schools, low interest in study, poor academic achievement, lack of personal cleanness, aggressive behaviors within schools and lack of basic literacy were identified by teachers among the school children for providing counseling services. Most of the teachers not satisfied about the counseling services provided to the students in their schools. Only 36.17% of schools, formulated committee for career guidance and counseling according to the MoE circular and 46.8% of schools have teachers for career guidance and counseling. Out of the sample, 44.68% of schools have “counseling cell”/ separate room for counseling. Further problems such as lack of efficient counseling services in schools, negative attitudes about counseling services among stakeholders, shortage of professional teachers for counseling services in schools and there is no proper monitoring mechanism at the zonal and provincial level. All teachers emphasizes the importance of counseling services for their schools. According to their perception, stakeholders in their schools such as principals, teachers, and students have different attitudes towards need for counseling services in their schools. There are several drawbacks identified by the teachers in the existing counseling services in their schools. Teachers were provide the suggestions for improving counseling services in the schools such as to appoint qualified teachers for counseling in each schools, to provide training for untrained counseling teachers, to conduct awareness regarding counseling for stakeholders such as schools principals, teachers, students and parents, to monitor the counseling services at schools, to start the village based counseling services for parents and their children and to maintain the follow-up services.
Keywords: Teachers; Perception; Counseling Services; Kilinochchi Educational Zone